A criação cinematográfica na educação estético-humanista do(a) professor(a) - YASMIN OLIVEIRA CABRAL (2022)
This research is linked to the Research Line Educational practices, training of teachers/educators in school and non-school spaces of the Graduate Program in Education of the Federal University of Mato Grosso do Sul – Campus do Pantanal ( PPGE UFMS/CPAN) and the research group Discourses and Poetic Practices in Education (UFMS-CPAN/CNPq). The study is theoretically based on the ideas of Lev Vygotsky (1896-1934), especially the centrality of experience (perezhivanie), organized in order to respect its aesthetic principles, to promote the expressive and poetic aggrandizement of individuals, making them increasingly capable of imagining and creating different worlds, with humanized relationships and actions. Theoretical studies on cinematographic art are also considered, which it presents as an area of knowledge with the potential to increasing the teacher’s aesthetic and humanist education. Considering the theoretical branch, this research’s main objective is to analyze the potential of cinematographic art for the aesthetic education, and therefore humanist, of the teacher; the following research actions were also envisioned: theoretically understanding the relationships between aesthetic experience, cinematographic creation and teacher training; experience the creation of a short film with teachers; to analyze the teachers' discourse on the formative potential of living with art, specifically with cinematographic creation considering the pandemic scenario. The research methodology covered two stages; the first consisted of a bibliographic study to develop the theoretical discussions intended in relation to Vygotsky's propositions on aesthetics, art and humanist training; the second is about an empirical study, a participant observation., that included debates on cinematographic creation and the production of two short films with a group of seven teachers; records were made about the experiences with the teachers and two semi-structured interviews with each praxis participant, at the beginning and end of the empirical process. The data show that cinematographic art has the potential to involve individuals in a collective process that enhances perezhivanie, especially through the possibility of move the subjects and your knowledge of realities/notions different from personal experiences. Art in the teacher’s’ professional development can also encourages voluntarism, which includes the will to create – a creation that can be meaningful within narratives, and perception of time and space, curriculum, and pedagogical proposals. Art also becomes powerful way to mediate the development of teachers' sensitivity, straining their ways of thinking and acting, opening gaps for more awareness; in the midst of training programs with the arts, teachers also felt compelled to express themes/subjects that needed to be addressed, theoretically and in more depth, in future training programs. About cinematographic art, in particular, and its potential for teacher training refers to the possibility of representing and recreating reality through reality itself; cinema strengthens the possibility of historical and social reading of the world, besides the poetic creation of them, because its compositions will involve people, beings, scenarios, themes, movements, lighting, sounds, which are close to life itself, presenting more persuasive potential, that is, convincing that it is necessary to analyze situations and create poetic ways of living that will strengthen the omnilateral development of the human being.